Safe food for a healthy India - Chand, Subhash (Yojana)
Food safety is no longer optional- it is essential for protecting public health, ensuring farmer livelihoods, and maintaining India's reputation in global markets. With coordination policy reform, technology adoption, and public education, India can build a resilient and trustworthy food system. - Reproduced
Keywords: food safety, health, FSSAI, global market